The singing method in teaching and learning process in helping students to master Arabic lexical - Mohd. Yusof, Sanitah (Serials Publications, 2016)
This research was conducted to examine the effect of using singing method in teaching and learning process, in helping students to master Arabic lexical items, by writing words, memorizing words and constructing sentences. The research was also carried out to find out the differences of achievement between genders after undergoing Arabic lesson using the singing method. It was a quantitative study with quasi-experimental design involving data obtained from pre-test and posttest. Two homogeneous groups known as treatment group and control group were formed to achieve these purposes. In this study, the treatment group had learned Arabic using the singing method, while the control group had learned Arabic using conventional or traditional method. The learning process for both group was carried out for four weeks. All data were analyzed using the IBM SPSS v. 21 through Levene's F-test to determine homogeneity of variances (data from pre-test) and t-test to determine the differences of achievement between groups (data from post-test). The results showed the treatment group significantly performed better than control group on writing words and memorizing words. However, there are no significant differences between both groups in building sentences. The results also indicated that the performance of both male and female in singing method group was almost similar in every aspects of vocabulary acquisition.